Empowering Parent Communities through "Rumah Literasi Digital": Technology-Based Supervision Training and Learning Mentorship in High-Density Residential Areas - Sudrajat, Didi; Sartinayanti, Sartinayanti; Yani, Ahmad; Sukmayadi, Dodi; Aprianto, Iwan (International Journal of Community Service (IJCS), 2026)
This qualitative study examines the effectiveness of a community-based digital literacy intervention—Rumah Literasi Digital (Digital Literacy House)—in empowering parents to supervise their children's digital learning in high-density residential neighborhoods. Through semi-structured interviews and focus group discussions with 32 parents and 8 educators from four community learning centers (CLCs) in Jakarta over an eight-month period, we applied Braun and Clarke's reflexive thematic analysis to explore how technology-integrated training programs foster parental empowerment across three dimensions: resource empowerment, critical awareness, and relational empowerment. Findings demonstrate that structured digital parenting interventions significantly enhance parents' capacity to identify and access digital resources, develop critical consciousness about technology risks, and strengthen family communication about online activities. Thematic analysis revealed five overarching themes: (1) Knowledge Construction and Digital Competency Development, (2) Critical Consciousness Formation, (3) Relational Networks and Peer Support, (4) Family Communication Enhancement, and (5) Systemic Barriers and Implementation Challenges. The study contributes evidence-based insights into community-based approaches for addressing the digital divide in resource-constrained urban contexts and offers actionable recommendations for integrating digital parenting literacy into non-formal education frameworks in Indonesia.